Potensi Limbah Kulit Udang dan Cangkang Kepiting Sebagai Chitosan Polymer Medium (CPM) - Hafidya Norista Pramesti; Yayok Suryo Purnomo; Aussie Amalia (Program Studi Teknik Lingkungan, Universitas Pembangunan Nasional Veteran Jawa Timur, 2022)
Crab shell and shrimp shell waste contains chitin which is considered to have the potential to become Chitosan Polymer Medium (CPM) as a mask coating material to remove toxic substances in cigarette smoke. Hazards that have been identified require several control measures to a point of safety. The way that can be used to control the dangers of cigarette smoke is to use a mask. Therefore, this study aims to determine the CPM characteristics of crab shells and shrimp shells that are useful as CPM. The analysis used is Scanning Electron Microscope (SEM) to determine the characteristics, and Fourier Transform Infrared (FTIR) to determine the structure and degree of deacetylation. The best results obtained from this study were Chitosan Polymer Medium (CPM) shrimp shells with a pore diameter of ± 0.31 m – 0.33 m with a high density and a degree of deacetylation of 82.10%.